PENGARUH PENDIDIKAN GIZI DENGAN POSTER DAN KARTU GIZI TERHADAP PENINGKATAN PENGETAHUAN DAN SIKAP ANAK TENTANG GIZI SEIMBANG DI SDN PLOSO I-172 SURABAYA - Sonya Hayu Indraswari (The Indonesian Journal of Public Health, 2019)
The prevalence of childhood obesity in Indonesia increase from year to year. This circumstance is believed to be associated with the high consumption of fatty foods and lack of knowledge of a balanced diet. Conducting the nutrition education of balance diet (nutrition counseling) is one of the ways to improve knowledge and attitude towards nutrition and to reduce nutritional problems. The study aims to analyze the effect of nutrition education by utilizing the poster and nutrition card on elementary students at SDN Ploso I-172 Surabaya. This study was Quasi-experimental research with pre-post test design involving 29 samples of elementary students at SDN Ploso I-172 Surabaya. The samples were chosen through a simple random sampling technique. The data were collected by interview using the questionnaire. The statistical test utilized the Paired Sample T-Test. The nutrition education with posters media increased the students’ knowledge (p=0.005) and attitude (p <0.001) on a balanced diet after the intervention. Similarly, in the case of nutrition education using nutrition card, there was an increase in knowledge (p=0.016) and attitude (0.002). The average students’ knowledge before they got nutrition education with poster media was 9.40, which then increased to 11.00, while the average students’ attitude score also increased from 71.47 to 78.20. The average students’ knowledge before they were given nutrition education with nutrition card media was 8.86 and increased to 11.57, the average students’ attitude value also increased from 72.21 to 79.28. In conclusion, there were the effects of nutrition education intervention using poster and nutrition card in improving the knowledge and attitude on balance diet of elementary students at SDN Ploso I-172 Surabaya